PENELITIAN KUAT UJI TEKAN BETON DENGAN MEMANFAATKAN LIMBAH BETON YANG TIDAK TERPAKAI - Herlan Pratikto; Rekso Ajiono (Kadiri University, 2017)
Concrete has many classifications and characteristics, from low-quality, medium to high-quality concrete. Along with the development of technology today many types of materials and mixtures are used. Additional materials include concrete that is not used. Tests of test objects in this study used a mixture of 10%, 15%, 20% and 25%. The variation is carried out at the age of 7, 21, and 28 days with the parameters used are only compressive strength. The results showed that the average compressive strength of concrete in each variation was 10% (22,155Mpa), 15% (17,514 Mpa), 20% (15,271 Mpa) and 25% (12,714 Mpa). With the target of K300 compressive strength, the result is mixed substitution with a maximum compressive strength percentage of 10% (22,155Mpa).Â